THE ROLE OF CULTURE AND SOCIAL FACTORS IN THE FORMATION OF SPEECH ETIQUETTE (Scientific journal of the Fergana State University, 2023)
This article examines speech etiquette and the role of national culture in its formation, the emergence of socially conditioned forms of speech behavior due to various images and traditions, the specifics of youth speech in oral speech, specific ways of establishing communication between speech common interlocutors, social factors influencing the formation of speech etiquette.